Reduction in non-abstinent WHO drinking risk levels and depression/anxiety disorders: 3-year follow-up results in the US general population - Knox, Justin; Mann, Karl (Drug and alcohol dependence, 2019)
Background - Non-abstinent drinking reductions that predict improvement in how individuals feel or function, such as the World Health Organization (WHO) drinking risk levels, may be useful outcomes in clinical trials for alcohol use disorders (AUD). - Methods - Current drinkers in a U.S. national survey (n = 22,005) were interviewed in 2001–02 (Wave 1) and re-interviewed 3 years later (Wave 2). WHO drinking risk levels, a 4- level categorization system (very-high-risk, high-risk, moderate-risk, and low-risk drinkers) defined using estimated mean ethanol consumption (grams) per day in the prior 12 months, and DSM-IV depressive and anxiety disorders were assessed at both waves. Logistic regression was used to produce adjusted odds ratios (aOR) testing the associations of changes between Wave 1 and Wave 2 WHO risk levels to the presence or persistence of depression and/or anxiety disorder by each initial Wave 1 risk level. - Results - Among Wave 1 very-high-risk drinkers, lower odds of depression and/or anxiety disorders at Wave 2 were predicted by reductions in WHO risk levels of one-, two- or three-levels (aOR = 0.42, 0.37, 0.67, p-values 0.04-<.0001), as was the persistence of depression and/or anxiety disorders among those with such disorders at Wave 1 (aOR = 0.37, 0.29, 0.51, p-values .03-<.0001). Results were less consistent for participants initially drinking at lower risk levels. - Conclusions - Among very-high-risk drinkers, reductions in the WHO drinking risk categories were associated with lower risk of depression and/or anxiety disorders. These results add to findings indicating reductions in WHO risk levels are a meaningful indicator of how individuals feel and function.
Gesehen am 21.05.2019